Advancing Porphyra linearis (Rhodophyta, Bangiales) culture: low cost artificial seawater, nitrate supply, photosynthetic activity and energy dissipation - Pereira, Débora Tomazi; Korbee-Peinado, Nathalie; Vega, Julia; López-Figueroa, Félix (Springer, 2024)
Fertilizer use in agriculture and aquaculture significantly contributes to nitrate-rich effluent discharge into aquatic environments. Porphyra's high surface area/volume enables efficient nutrient assimilation. This study aimed to identify a cost-effective, efficient artificial seawater medium for Porphyra linearis cultivation and determine the optimal nitrate concentration to enhance photosynthetic activity. Porphyra linearis was grown in three different salt media, with photosynthetic and biochemical parameters assessed, showing no differences. The nitrate experiment (7 days) using low-cost salt and varied concentration (0 to 6.5 mM) revealed optimal nitrate uptake at 3 and 5 mM, while 6.5 mM indicated saturation/toxicity. The phycobiliproteins contents did not increase compared to the 0 mM, but exhibited greater functionality, as evidenced by the enhanced photosynthetic parameters. Chlorophyll a peaked in 3 mM, whereas lutein and β-carotene peaked in 0 and 3 mM. The thalli turned greenish and appeared to have degraded branches under 0 mM. Growth rate was the same under all nitrate concentration and higher than under 0 mM. The presence of nitrate increased ETRin situ and ETRmax, whereas the absence decreased the range between optimal irradiance for photoinhibition (EoptETR) and saturated irradiance for photosynthesis (EkETR) and between saturated irradiance for non-photochemical quenching (EkNPQ) and EkETR, suggesting that under more nitrate available the algae dissipate less energy. P. linearis showed a wide range of nitrate use without variation in pigment composition in contrast to photosynthetic capacity. The 1.5 and 3 mM in cultivation significantly enhance the photosynthetic response of P. linearis, supporting their potential application in IMTA and bioremediation.
Keywords: Cultivos y agua; Ecología; Biotecnología; Geología; Nitrate assimilation; Bioremediation; Integrated multi-trophic aquaculture; Photosynthetic antennae; Pigments